The Study of Vocal Function in Patients With Early Laryngeal Carcinoma After Transoral Laser Microsurgery - Arezoo Hasanvand; Akbar Darouie; Samira Aghadoost; Payman Dabirmoghaddam; Enayatollah Bakhshi (University of Social Welfare and Rehabilitation Sciences, 2023)
Objective Today transoral laser microsurgery is considered as one of the first options to control early laryngeal cancer, and voice disorder is one of the inevitable complications of this therapeutic component. This study aimed to compare the vocal function in patients with early-stage laryngeal cancer following laser surgery with healthy individuals with normal voice quality using acoustic analysis and the voice handicap index and to examine the correlation between the results of these two evaluations in each group. Materials & Methods The current research is a descriptive-correlational and comparative study that was cross-sectioned using convenience sampling into two groups consisting of 60 men (Mean±SD of age 59.18±5.170 years) with early laryngeal cancer undergoing laser surgery as a patient group and 60 men (Mean±SD of age 56.68±5.491 years) with normal voice quality, and without any history of voice disorder as a control. The vocal function of participants was assessed using acoustic parameters (including jitter, shimmer, harmonic to noise ratio, fundamental frequency, smoothed cepstral peak prominence) and a 30-item Persian version of the voice handicap index questionnaire (including overall score and scores of physical, emotional and functional subscale). Then, data were analyzed using SPSS software, version 20, descriptive statistics, Kolmogorov-Smirnov, independent t-test, and Pearson correlation coefficient at the P<0.05. Results The results show that the acoustic parameters and voice handicap index in the group undergoing laser surgery are significantly different from the control group (P<0.001). Also, a significant direct correlation between jitter and shimmer with total score and physical subscale of VHI, a significant inverse correlation between the harmonic-to-noise ratio and total score, functional and physical subscales of VHI, as well as between smoothed cepstral peak prominence with total score and all subscales of VHI (P<0.05). In addition, in the control group, there is no significant correlation between the acoustic parameters and the subscales of the voice handicap index (P<0.05). Conclusion The findings of the acoustic analysis and the voice handicap index show impairment in vocal function and a decrease in voice-related quality of life (QoL) in patients with early laryngeal cancer after laser surgery. Furthermore, a significant correlation between the scores of the voice handicap index and acoustic analysis parameters, especially cepstral analysis indicates the necessity to pay attention to frequency-based analysis. Therefore the results of the present study emphasize the need for a comprehensive assessment of vocal function, providing voice therapy programs, and attention to psychological problems in patients with early laryngeal cancer after laser surgery.